Pengaruh Harga dan Desain Produk terhadap Keputusan Pembelian Busana Muslim - Ach Agil Dzikrullah; Rahayu Mardikaningsih (Dharma Ekonomi, 2024)
This research aims to determine the influence of price and product design on Muslim clothing purchasing decisions. In the fashion industry, especially Muslim fashion, price and product design are two very important factors in influencing consumers' decisions to make purchases. Competitive and affordable prices can attract consumers' attention, while attractive designs that are in line with trends can increase the product's appeal. Through the literature review method, this research analyzes various relevant scientific sources to explore the relationship between price, product design and purchasing decisions. The research results show that reasonable prices and innovative product designs have a significant contribution to consumer purchasing decisions. Consumers tend to prefer to buy Muslim clothing that offers a combination of attractive prices and designs that suit their preferences. Therefore, Muslim fashion companies and related parties are expected to continue to pay attention to appropriate pricing strategies and develop attractive product designs. In this way, companies can create an environment that supports improved purchasing decisions, which ultimately contributes to sales success and sustainable business growth.